Integration and implementation of process controls and quality procedures on the shopfloor of semi-conductor backend process - Low, Hong Nyi. (2008)
This project aimed to provide real time information required for management decisions and planning. It has to start with integration of various processes and controls over manufacturing shop-floor (semi-conductor sector), to achieve common the critical success factor of the organization.